Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Kinerja Pegawai Negeri Sipil pada Kantor Walikota Pemerintah Kota Medan - Arasy Ayu Setiamy (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
This study is a quantitative study where the population in this study was 709 employees and the sampling in this study used the slovin formula where the sampling was only 5% of the total population, namely 256 respondents. The study used a survey method for distributing questionnaires in order to find out the results of this study. The results of this study are the influence of leadership style (X1) and work discipline (X2) on the performance of civil servants (Y) with a constant value of 4.732 where these results are searched by using multiple linear regression data analysis techniques and processed with SPSS, as for the hypothesis In this study, H1 was accepted and Ho was rejected because of the significant influence between leadership style and work discipline on the performance of civil servants with a significant level of 0.000 <0.05